Taxonomy and the unusual morphological similarity among Hypocerides Schmitz species (Diptera: Phoridae) - Ament, Danilo César (Zootaxa, 2021)
Hypocerides Schmitz comprises seven species of considerable morphological similarity according to authors that described or reviewed material from the genus. This lack of variation is problematic for its taxonomy as little is known about which structures could be evidence for species recognition or even about which sex is the most informative to its species-level taxonomy. In this study, I examined males and females of the genus from the Neotropical, Nearctic, and Palearctic Regions in search of informative morphological characters for the genus taxonomy. The examination included types of five of the seven known species and new material from the Neotropical Region and Madagascar. I present a detailed description of the genus, illustrate some of its structures for the first time, and compare the morphology of the specimens examined. Few morphological differences were found but none was considered sufficient to infer species limits. This morphological uniformity among species from different biogeographic regions can be seen as evidence that they could all be one species with an almost worldwide distribution. The low morphological variation among Hypocerides species and their apparent wide distributions remain interesting biological questions.